1999
DOI: 10.1007/s001099900063
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene I/D polymorphism and renal disease

Abstract: In recent years a vast amount of data has been published on the association between the insertion/deletion (I/D) polymorphism of the gene coding for angiotensin-converting enzyme and renal disease. It has become clear that the polymorphism does not affect the prevalence of renal disease. However, data on the association with progression of renal disease and therapy response are still contradictory. Moreover, sufficient data on the physiological significance of this polymorphism are still lacking. This contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 97 publications
1
24
0
2
Order By: Relevance
“…2,3 Although the exact mechanism of the ACE gene polymorphism related to the progression of renal disease remains unclear, several studies have demonstrated a more progressive renal functional decline in patients with DD genotype of ACE gene and chronic renal failure. 12,[15][16][17] However, this relationship is controversial in some studies. 18,19 It has been suggested that DD genotype can have some impact on the rate of renal function loss, but that the impact of the genotype can be obscured by other risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Although the exact mechanism of the ACE gene polymorphism related to the progression of renal disease remains unclear, several studies have demonstrated a more progressive renal functional decline in patients with DD genotype of ACE gene and chronic renal failure. 12,[15][16][17] However, this relationship is controversial in some studies. 18,19 It has been suggested that DD genotype can have some impact on the rate of renal function loss, but that the impact of the genotype can be obscured by other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that high local AII concentrations as a result of deletion polymorphism of the ACE gene is associated with proteinuria in chronic renal diseases. 12 To our knowledge, there are limited studies on the possible role of ACE gene polymorphism in children with minimal change nephrotic syndrome (MCNS). The aim of this study was to investigate possible relationship between the ACE gene I/D polymorphism and clinical and laboratory findings of MCNS.…”
Section: Introductionmentioning
confidence: 99%
“…7). Studies have found that the DD genotype is associated with a more rapid loss of renal function in diabetic nephropathy, 23 IgA nephropathy 24 and adult polycystic kidney disease, 25 when compared to the II or DI genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several studies have shown that the DD genotype is associated with more rapid progression and severity of diabetic and immunoglobulin A nephropathy (reviewed in Ref. 7). The observed beneficial effects of ACE inhibitors in experimental BMT nephropathy and the association of ACE genotype with progression of other renal diseases led us to ask whether ACE genotype is associated with loss of renal function after BMT.…”
mentioning
confidence: 99%
“…Kiterjedt vizsgálatokat végeztek mind kardiológiai, mind vesebeteg populációkon [6]. Egyes genotípusok kedvezőtlen prognosztikai faktorként szerepelnek a szív-ér rendszeri megbetegedés tekintetében, és sok szerző a CAN nem immunológiai rizikótényezőjeként is tekint rájuk.…”
Section: The Effect Of the I/d Polymorphism Of The Angiotensin-converunclassified